Implicit anticipation of probabilistic regularities: Larger CNV emerges for unpredictable events. (18th June 2021) - Kóbor, Andrea; Kardos, Zsófia; Horváth, Kata; Janacsek, Karolina; Takács, Ádám; Csépe, Valéria; Nemeth, Dezso
Abstract: Anticipation of upcoming events plays a crucial role in automatic behaviors. It is, however, still unclear whether the event-related brain potential (ERP) markers of anticipation could track the implicit acquisition of probabilistic regularities that can be considered as building blocks of automatic behaviors. Therefore, in a four-choice reaction time (RT) task performed by young adults ( N = 36), the contingent negative variation (CNV) as an ERP marker of anticipation was measured from the onset of a cue stimulus until the presentation of a target stimulus. Due to the probability structure of the task, target stimuli were either predictable or unpredictable, but this was unknown to participants. The cue did not contain predictive information on the upcoming target. Results showed that the CNV amplitude during response preparation was larger before the unpredictable than before the predictable target stimuli. In addition, although RTs increased, the P3 amplitude decreased for the unpredictable as compared with the predictable target stimuli, possibly due to the stronger response preparation that preceded stimulus presentation. These results suggest that enhanced attentional resources are allocated to the implicit anticipation and processing of unpredictable events. This might originate from the formation of internal models on the probabilistic regularities of the stimulus stream, which primarily facilitates the processing of predictable events. Overall, we provide ERP evidence that supports the role of implicit anticipation and predictive processes in the acquisition of probabilistic regularities. Highlights: Implicit acquisition of probabilistic regularities was measured in a cued RT task. The CNV developed during the presentation of an unspecific cue until target onset. The CNV amplitude was larger before unpredictable than before predictable targets. Anticipation of unpredictable targets possibly required more attentional resources. Internal models on predictability could have guided these anticipatory processes.